What is Inclusive Development? Introducing the Multidimensional Inclusiveness Index - Christoph Dörffel; Sebastian Schuhmann (Social Indicators Research, 2022)
Despite decreasing global poverty, feelings of increasing inequalities drive growing dissatisfaction with development outcomes. Inclusive development benefiting larger parts of societies will be perceived as more legitimate. Yet, there is neither a thorough agreement on what constitutes inclusive development nor a convenient measurement tool. The purpose of this paper is to address both these shortcomings in the literature. We derive a notion of inclusive development that is human-based and acknowledges all factors important for well-being. With the introduction of the Multidimensional Inclusiveness Index (MDI), we address the conceptual drawbacks of prominent approaches like the Human Development Index (HDI), Inequality-Adjusted Human Development Index and Inclusive Development Index (IDI) and extend the available data sample (by 50% compared to the HDI). The MDI consists of two subindices—one on development equity and development achievements each—and is calculated in three versions for up to 171 countries for the years 1960–2018. By applying principal component analysis, we rely on the structure of the underlying data for the aggregation of the 14 variables into the subindices. The subindices are aggregated by geometric mean. We show that regional development patterns are captured and major political events reflected in MDI country trends. Despite correlations resulting from data similarities, the MDI provides new insights when compared to HDI, IDI and gross domestic product . All three MDI versions display increasing global averages over time. These positive trends are largely driven by improvements in the achievements dimension. Despite optimistic trends in recent years, equity considerations deserve a stronger emphasis in development concepts.
Keywords: O15; C43; P48; 300; Index; Multidimensional; Inclusiveness; Inclusive development